Assessing the Economic Impacts of Climate Change on Agriculture in Egypt : A Ricardian Approach - Eid, Helmy M.; El-Marsafawy, Samia M.; Ouda, Samiha A. (World Bank, Washington, DC, 2012)
This study employed the Ricardian approach to measure the economic impacts of climate change on farm net revenue in Egypt. Farm net revenue were regressed against climate, soil, socioeconomic and hydrological variables to determine which factors influence the variability of farm net revenues. 900 households from 20 governorates were interviewed. The standard Ricardian model was applied, in addition to three other models, each representing an adaptation option that could be used to reduce the harmful effects of temperature stress. A further adaptation strategy was tested: raising livestock on the farm to cope with the harmful effects of climate change. Besides this, the effects of two climate change scenarios (using MAGICC/SCENGEN and GCMs-General Circulation Models) were considered. The results from the two climate change scenarios showed that high temperatures will constrain agricultural production in Egypt. Irrigation and technology are therefore the recommended adaptation options. However, warming may also affect water resources and that would pose another problem for agricultural production. A policy should be developed to cope with the adverse effects of climate change on agriculture. It should focus on three areas: crop management, water management, and land management. The favored option for adapting to increased temperatures is irrigation. Some farmers adjust their crop sowing dates to avoid the expected high temperatures. To adjust to shortages in rainfall, farmers use crop varieties with high water use efficiency and early maturing varieties.